Propostas de regulamentaç\~ao do lobby no Brasil: Uma análise comparada - Manoel Leonardo Santos; Lucas Cunha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Lobbying regulation initiatives have been developed, especially in liberal democracies, based on two main questions. The first refers to the most powerful interest groups' advantages in the political process in comparison to others who do not have the necessary resources to professionalize their activities. The second question is about the broadly shared perception about unethical conducts and the uneven power to influence public agents that some private interest representatives have when there is interaction. In order to face the issue, many countries that regulated lobbying activities based their legislations on transparency and accountability as a way of minimizing the problem (Thomas, 2004). This study verifies how Brazilian legislators have absorbed these questions in the many attempts to regulate lobbying activities in the country since 1984. From a comparative analysis of 12 law initiatives and the legislation from 9 countries, we conclude that there is a rich set of propositions in Brazil and that our legislators choose an intermediate regulation, compatible with other countries with similar characteristics. Lastly, this study offers recommendations about relevant aspects of the debate, if the theme receives the necessary attention to be in the political reform agenda.
Keywords: D72; 330; regulation; lobby; Congresso Nacional; comparative study; interest groups